AL-I’JAZ BAYNA AL-TAHLIL WA AL-TALAQQI LADAY ‘ULAMA’ AL-QARNAYN AL-RABI’ WA AL-KHAMIS - Abeer Obeid Al-Shbiel; Qusaiyen Aly (Universitas Islam Negeri Ar-Raniry, 2019)
There are various reasons for our choice of this period of the scientific Arab history: the first is the richness in thought, culture, philosophy and experimentation, following the internationalization of the peoples of the Abbasid Caliphate. The second is the maturity of the individual creative tools of scientists in most fields of knowledge, especially in the linguistic ones which formed the basis from which all Arab sciences sprang. Based on the above, we follow the analytical methods of miracle scholars. The first of these scholars was Ramani, who was interested in individual performances and in rhetorical art in its individuality. The second was Abu Suleiman al-Khattabi, who preoccupied himself with researching in the depths of the problem. The third was Baqalani Abu Bakr Muhammad, the author of the theory of equanimity and inequality. The fourth was judge Abduljabbar who tried to link between the mind and language. The fifth was Abdulqahir Al-Jerjani, the founder of the theory of systems. Indeed each of these scholars has studied the issue of Quranic miracle in a way which suited their methods, and then discussed the ways his views were received in private and in public. We claim that we have paid special attention to the specificity of grammar as a basis, for all of them, for the study of miracles, and none of them has been freed from the study of poetry. However, Al-Jarjani attributed poetry as the necessary basis for the knowledge of miracles, and we did come out with some conclusions which we have noted at the end of our research.